An chromosome-level haplotype-resolved genome assembly and annotation of pitaya (Selenicereus polyrhizus) - Juncheng Li; Wenlong Luo; Biao Jiang; Satish Kumar; Mengfei Lin; Qingming Sun (Scientific Data)
Abstract Pitaya, (Selenicereus spp.), a fruit originating from North and Central America and extensively cultivated in China and Vietnam, holds significant economic value. Utilizing PacBio HiFi sequencing and Oxford Nanopore Technologies ultra-long sequencing, aided by Hi-C data, we have assembled a chromosome-level haplotype-resolved genome. The sizes of the two haplotype genomes were determined to be 1.477 Gb (hap1, contig N50 = 133.35 Mb) and 1.442 Gb (hap2, contig N50 = 132.57 Mb), with 96.7% (hap1) and 98.4% (hap2) respectively allocated to 11 pseudochromosomes. Hap1 comprises 58.94% repeat sequences and predicts a total of 29,139 protein-coding gene models and 18,378 non-coding RNAs. Hap2 comprises 58.37% repeat sequences and predicts a total of 28,538 protein-coding gene models and 19,458 non-coding RNAs. Notably, 93.5% and 93.6% of protein-coding genes were annotated for the two haplotypes. The high-quality genome assembly presented in this study provides a valuable resource for future ecological, evolutionary, biological, and breeding research in pitaya.